Prevalence of chest trauma, associated injuries and mortality: a level I trauma centre experience. - Veysi, Veysi T; Nikolaou, Vassilios S; Paliobeis, Christos; Efstathopoulos, Nicolas; Giannoudis, Peter V (Int Orthop, 2009)
A review of prospectively collected data in our trauma unit for the years 1998-2003 was undertaken. Adult patients who suffered multiple trauma with an Injury Severity Score (ISS) of >/=16, admitted to hospital for more than 72 hours and with sustained blunt chest injuries were included in the study. Demographic details including pre-hospital care, trauma history, admission vital signs, blood transfusions, details of injuries and their abbreviated injury scores (AIS), operations, length of intensive care unit and hospital stays, Injury Severity Score (ISS) and mortality were analysed. Fulfilling the inclusion criteria with at least one chest injury were 1,164 patients. The overall mortality reached 18.7%. As expected, patients in the higher AIS groups had both a higher overall ISS and mortality rate with one significant exception; patients with minor chest injuries (AIS(chest) = 1) were associated with mortality comparable to injuries involving an AIS(chest) = 3. Additionally, the vast majority of polytraumatised patients with an AIS(chest) = 1 died in ICU sooner than patients of groups 2-5.
Keywords: Adult; Female; Humans; Injury Severity Score; Male; Middle Aged; Prevalence; Prospective Studies; Survival Rate; Thoracic Injuries; Trauma Centers; United Kingdom; Wounds, Nonpenetrating; Young Adult